Investigating the Experimental Limits of the Brewster’s Angle Method - Sümer, Can; Kuştepeli, Alp; Kuştepeli, Alp; Dinleyici, Mehmet Salih; Dinleyici, Mehmet Salih (Türkiye Klinikleri Journal of Medical Sciences, 2018)
We present the method, analysis, and experimental results of the Brewster’s angle method commonly used for determining the refractive indices of optical films. We show the significance of the intersection of reflectance curves, in that the necessity for substrate refractive index and film layer thickness knowledge are both eliminated. We present the conditions for the existence of the second intersection of reflectance curves and introduce a method for determining the refractive index of the substrate layer by using the angular information alone. Analytical results reveal impressive practical sensitivity and accuracy limits for the method, where the experimental results also support the theoretical analysis.
Keywords: Brewster’s angle; Nondestructive measurement; Optical film; Refractive index